2006
DOI: 10.1136/thx.2004.033266
|View full text |Cite
|
Sign up to set email alerts
|

Addition of salmeterol to existing treatment in patients with COPD: a 12 month study

Abstract: Background: This study investigated the addition of salmeterol to existing treatment for exacerbations in patients with poorly reversible chronic obstructive pulmonary disease (COPD). Methods: 634 patients aged .40 years with a history of COPD exacerbations (including at least two in the previous year) and poor reversibility of airflow obstruction ((10% predicted forced expiratory volume in 1 second) received either salmeterol 50 mg or placebo twice daily from a Diskus inhaler for 12 months. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 25 publications
0
54
0
2
Order By: Relevance
“…Previous studies have shown that the addition of the LABA salmeterol results in a decrease in the exacerbation rate, improved health status, an increase in forced expiratory volume in 1 s (FEV 1 ) and in a reduction of lung hyperinflation at rest and during exercise [13,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the addition of the LABA salmeterol results in a decrease in the exacerbation rate, improved health status, an increase in forced expiratory volume in 1 s (FEV 1 ) and in a reduction of lung hyperinflation at rest and during exercise [13,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that this stabilization approach may have benefits for trials compared with withdrawing maintenance therapy during run-in. In particular, it may improve detection of clinically important changes in health status, and reduce the proportion of withdrawals during run-in (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Reliance on ''as needed'' therapy is not appropriate in COPD [30], and the major benefit of longacting inhaled bronchodilators is not due to an increase in potency but to duration of action [31]. Both b-agonists and anticholinergics abolish resting airway tone and improve airflow during extended periods of use [32,33]. Combining these drugs produces the following additional benefits.…”
Section: Drugs and The Secondary Prevention Of Copdmentioning
confidence: 99%